ANALISIS KESALAHAN MORFOLOGI PADA KOMENTAR NETIZEN DALAM UNGGAHAN ISU PENDIDIKAN DI INSTAGRAM @ ditjen.gtk.Kemdikbud - Auli destianika; Indah Sulmayanti; Dian Kurnia Wati; Bunga Nulita Sari; Asep Suryadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the forms of morphological errors found in netizens' comments on educational issue posts published on the Instagram account @ditjen.gtk.kemdikbud. The research employed a qualitative descriptive method using a purposive sampling technique by selecting comments that were relevant to educational issues and indicated morphological errors. The findings revealed several types of morphological errors, including affixation errors, the use of non-standard abbreviations and shortened words, errors in writing reduplication, phoneme omission, and the use of word forms that do not conform to the standard rules of the Indonesian language. The most dominant errors were the use of abbreviations such as yg, utk, tdk, and dr, as well as the use of numerals to represent reduplication, such as guru2 and rekan². These findings indicate that language use on social media tends to prioritize practicality over adherence to standard linguistic rules. This study is expected to contribute to linguistic studies, particularly in the field of morphology, and to raise public awareness of the importance of using proper and standard Indonesian in digital communication.